Defining a role for lung function associated gene GSTCD in cell homeostasis - Amanda P. Henry; Kelly Probert; Ceri E. Stewart; Dhruma Thakker; Sangita Bhaker; Sheyda Azimi; Ian P. Hall; Ian Sayers (Respiratory Research, 2019)
Abstract Genome wide association (GWA) studies have reproducibly identified signals on chromosome 4q24 associated with lung function and COPD. GSTCD (Glutathione S-transferase C-terminal domain containing) represents a candidate causal gene in this locus, however little is currently known about the function of this protein. We set out to further our understanding of the role of GSTCD in cell functions and homeostasis using multiple molecular and cellular approaches in airway relevant cells. Recombinant expression of human GSTCD in conjunction with a GST activity assay did not identify any enzymatic activity for two GSTCD isoforms questioning the assignment of this protein to this family of enzymes. Protein structure analyses identified a potential methyltransferase domain contained within GSTCD, with these enzymes linked to cell viability and apoptosis. Targeted knockdown (siRNA) of GSTCD in bronchial epithelial cells identified a role for GSTCD in cell viability as proliferation rates were not altered. To provide greater insight we completed transcriptomic analyses on cells with GSTCD expression knocked down and identified several differentially expressed genes including those implicated in airway biology; fibrosis e.g. TGFBR1 and inflammation e.g. IL6R. Pathway based transcriptomic analyses identified an over-representation of genes related to adipogenesis which may suggest additional functions for GSTCD. These findings identify potential additional functions for GSTCD in the context of airway biology beyond the hypothesised GST activity and warrant further investigation.